Sosialisasi Tentang Penyakit Gastritis Di Posbindu Sido Rejo Kec Kabawetan Kab Kepahiang - Ariani, Winda; Sari, Puput Puspita; Sari, Leka Julita; Sari, Ezi Mareta; Murwati, Murwati; Wulandari, Wulandari; Rohani, Tuti; Azissah, Danur (Jurnal Kewirausahaan & Inovasi, 2025)
emergence of disease can be caused by lifestyle or lifestyle and food consumption patterns, which can cause health problems, one of which is stomach disorders, such as ulcers. Gastritis or dyspepsia, commonly known as ulcers, is a condition consisting of a number of symptoms that are felt as discomfort in the upper part of the stomach or heartburn. People who experience this condition often experience nausea, vomiting, dizziness, a sensation of fullness, and discomfort.